Litter expansion alters metabolic homeostasis in a sex specific manner. - Kavitha Kurup (Public Library of Science (PLoS), 2021)
Nutritional manipulations early in life have been shown to influence growth rate and elicit long lasting effects which in turn has been found to impact lifespan. Therefore, we studied the long-term effects of pre-weaning dietary restriction implemented by litter expansion (4, 6, 8, 10, and 12 pups per dam: LS4, LS6, LS8, LS10, LS12) on male and female C57BL/6J mice. After weaning, these mice were fed ad libitum a commercial lab chow for the 15-month duration of the study. The male mice from large litter size (LS12) were significantly leaner and had reduced total fat mass compared to the normal size litters (LS 6) starting from weaning through to 15 months of age. Male LS10 & 12 mice also showed significant reduction in their fat depot masses at 15 months of age: gonadal, subcutaneous, and brown fat whereas the females did not mimic these findings. At 9 months of age, only male LS12 mice showed improved glucose tolerance and male LS12 mice also showed improved insulin tolerance starting at 5 months of age. In addition, we found that the male LS8, 10 & 12 mice at 15 months of age showed significantly reduced IGF-1 levels in the serum and various other organs (liver, gastrocnemius and brain cortex). Interestingly, the female LS8, 10, 12 mice showed a different pattern with reduced IGF-1 levels in serum, liver and gastrocnemius but not in the brain cortex. Similarly, the litter expanded mice showed sex specific response to levels of FGF21 and adiponectin with only the male mice showing increased FGF21 and adiponectin levels at 15 months of age. In summary, our data show that, litter expansion results in long-lasting metabolic changes that are age and sex dependent with the male mice showing an early and robust response compared to female mice.